Nuclear cloning, stem cells and epigenetic reprogramming - Jaenisch, Rudolf (Henry Stewart Talks, 2007)
Transfer of somatic cell nuclei into enucleated oocytes for full term development of mammals, genomic reprogramming, the use of ES cells, terminally differentiated lymphoid cells, neurons and cancer cells as donors for nuclear transplantation, use of Somatic Cell Nuclear Transfer (SCNT) for "therapeutic cloning", scientific evidence vs. moral arguments
Reviewed at 2015/09/21, Archived at 2025/05/28